Rhetorical structure mastery of tertiary students’ speech: Challenges and possible solutions - Syafryadin Syafryadin; Andy Makhrian; Dian Eka Chandra Wardhana (Studies in English Language and Education, 2023)
Rhetorical structure in speaking is essential to guiding students through speaking and making public speeches. Thus, this research explores the students’ mastery of rhetorical structure in making a speech, their challenges, and potential solutions. A mixed method with an explanatory design was employed to achieve the objectives. The data were collected through a speaking test and interviews using instruments validated by peer researchers. The data were analysed quantitatively and qualitatively; while the quantitative data were analysed using a simple statistical analysis, the qualitative data were examined using several stages, namely data reduction, data display, and conclusion. The results show that the students’ average mastery of the rhetorical structure of speaking was not significantly high. Some students faced challenges such as language problems and problems with rhetorical structures. Language issues were articulated in grammar, anxiety, and the excessive use of fillers. The rhetorical structure became problematic because the students were unfamiliar with how to attract the audience when making a speech, they insufficiently used supported illustrations in their speech, and they rarely concluded their speech. The possible solutions to those challenges include training in public speaking and continual guidance from their lecturers. With the guidance of the lecturers, it is anticipated that the students will be able to implement the three components of speech to deliver more convincing speeches.